ANALISA STP (SEGMENTASI, TERTARGET DAN POSISI) PADA PENGEMBANGAN UNIT USAHA MANDIRI PESANTREN - Napisah Napisah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2022)
Positioning the pesantren's social position in the social context, would enable pesantren to obtain additional functions rather than only as a center for religious education, namely as a center for the development of a people's economy, which of course begins with strengthening the pesantren's own independent economic system. This study aims to determine the marketing strategy for developing pesantren business units based on STP (Segmenting, Targeting and Positioning) analysis. This research was conducted in one of the Islamic boarding schools located in West Java, namely the Riyadlul Ulum Wadakwah Condong Islamic Boarding School, Tasikmalaya. The research method used in this research is descriptive qualitative with observation, interview and documentation techniques. The results of the study confirmed a number of findings including, Islamic boarding schools have a number of consumer groups identified as users of the products to be produced. Consumers have a number of needs that can be met by pesantren, so that pesantren can implement more effective marketing efforts; Islamic boarding schools have a clear target market (targeted) from the type of business they run and pesantren occupies a distinctive position (compared to other business competitors) in the minds of consumers.